Uridine diphosphate-glucose 4-epimerase encoding gene galE affects the pathogenicity and carbon metabolism of Ralstonia pseudosolanacearum - ZHANG Hong; LIN Zhijian; ZHU Jindong; LIN Zhaomiao; LI Guoliang; XU Yongqing; LIU Zhonghua; QIU Yongxiang; QIU Sixin (浙江大学学报. 农业与生命科学版, 2023)
In order to clarify the pathogenic function of uridine diphosphate (UDP)-glucose 4-epimerase encoding gene galE on Ralstonia pseudosolanacearum, the association between galE and the pathogenic-related phenotypes, and the gene deletion effect on physiological and biochemical metabolism of R. pseudosolanacearum were explored by constructing galE gene knock-out strain ΔgalE and its complementary strain CΔgalE. The results showed that the deletion of galE gene significantly decreased the pathogenicity of R. pseudosolanacearum on sweet potatoes and affected pathogenic-related phenotypes. The colony fluidity, swimming mobility, exopolysaccharide content and biofilm formation of ΔgalE reduced compared to those of wild-type SPRS911 and CΔgalE. In the galactose metabolism pathway, after deletion of galE gene, the expression levels of galU, pgm, and glk genes involved in the metabolism between uridine diphosphate glucose (UDPG) and glucose decreased, and D-glucose 6-phosphate accumulated. The expression levels of UDP-galactose (UDP-Gal) metabolism related genes dgoK, dgoAa, dgoAb, malZ and galM increased. The deletion of galE gene also enhanced the assimilation of malic acid in R. pseudosolanacearum. These results indicate that the galE gene has significant effects on the pathogenicity and the carbon metabolism of R. pseudosolanacearum.